Design and Development of an Automatic Control System for a 433 MHz Yagi Antenna for Radiosonde Observation Stations Based on Android - Pratama, Saniku Arkham; Imammuddin, Azam Muzakhim; Novianti, Atik (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
Aerial observation plays a critical role in transportation, agriculture, and fisheries. Radiosondes, which are equipped with radio transmitters, provide essential atmospheric data such as air pressure, temperature, and humidity. Despite their importance, the receiving stations is for radiosondes face challenges related to antenna sensitivity and alignment, resulting in reduced data accuracy. This study focuses on the design and construction of an auto-control system for a 433 MHz Yagi antenna, integrated with an Android application for real-time monitoring. The system employs precise azimuth and elevation tracking, that significantly enhancing its ability to maintain an optimal position relative to radiosonde movements. Experimental results, indicate that the system achieves an average azimuth error of 3.03% and a corresponding accuracy of 96.96%, while elevation tests show an error of 2.27% with an accuracy of 97.72%. These findings highlight the potential of the proposed system in improving data quality and reliability in radiosonde applications.